Flood disaster and risk anticipation strategy. (February 2019) - Halim, H; Arifin, A; Nonci, N; Zainuddin, R; Anriani, H B; Kamaruddin, S A
Abstract: The purpose of this study is to describe the risk anticipation strategy in facing flood as an action by local people particularly in the settlement area of Makassar suburbs. This is urgent to describe due that flood area is the densely populated area. This research used interviews, observation and literature study. Interviewing is for residents about their strategy in anticipating the risk of floods. Results of interviews that are mapped are based on the indicators of risk anticipating strategy. Observation technique is about the settlement condition before and after the flood. Literature study is about related theory and the same problem of this research for comparing each other. This study found that the residents as local people in risk anticipating flood as strategy, such as refuge to relatives and neighbors whose homes are free of the flood, store goods on higher ground, or tie to keep them from flood flowing, pet animals, preparing rubber tires for transportation.